The Top-100 Highly Cited Original Articles on Drug Therapy for Ventilator-Associated Pneumonia - Wang, Chao-Yang; Li, Bing-Hui; Ma, Lin-Lu; Zhao, Ming-Juan; Deng, Tong; Jin, Ying-Hui; Ren, Xue-Qun (Frontiers in Pharmacology, 2019)
ABSTRACT Background In recent decades, research on drug therapy for ventilator-associated pneumonia remains one of the major hot-spots in the field of critical care medicine, but relevant data are not satisfactory. Our aim was to assess the status and trends of the most cited articles on drug therapy for ventilator-associated pneumonia through bibliometric approaches. Methods The Institute for Scientific Information (ISI) Web of Science core collection database was searched for the VAP-related articles using computer. The time period for retrieval was from the beginning of the database to September 30, 2018. The top 100 most cited articles were selected to obtain their information on the authors, title, publication, number of citations, author’s affiliations, country, etc. These general information and bibliometric data were collected for analysis. The VOSviewer software was used to generate a term co-occurrence graph that visualized a reference pattern for different terms in the 100 articles. Results The number of citations for the 100 selected articles ranged from 142 to 3218. These articles were published in 31 different journals. The top 3 journals in terms of the number of our selected articles they published were “CRITICAL CARE MEDICINE” (17 articles), “AMERICAN JOURNAL OF RESPIRATORY AND CRITICAL CARE MEDICINE” (11 articles) and “CLINICAL INFECTIOUS DISEASES” (10 articles). The most frequently nominated author was Kollef MH from the University of Washington, and of the top 100 articles, 16 listed his name. These top 100 articles were published after the year of 2000. The most common type of these articles was the Article (53%). The United States and France were major countries in researching drug therapy for VAP and have made significant contributions to the combat against ventilator-associated pneumonia. Gram-negative bacilli, pseudomonas-aeruginosa, antibiotics, risk factors and other terms appeared more frequently, suggesting that attentions on this issue currently focused on the rational application and management of antibiotics. Conclusions This study analyzed the 100 most cited articles on drug-treated ventilator-associated pneumonia, and provided insights into the historical developments and characteristics of the most cited articles in VAP field.